Sri Lanka Elderly Study: Phase 1 (SLES:1) – A descriptive study of the health status and physiological parameters of institutionalized elderly in Colombo district: The protocol - Amarasiri, W.A.D.L.; Atapattu, P.M.; Dalpatadu, K.P.C.; Dissanayake, W.D.N.; Fernando, A.D.A.; Fernando, N.H.D.; Gunatilake, M.; Jayawardena, R.; Jayaweera, S.K.; Kumarasiri, M.A.H.P.; Ranawaka, H.A.R.; Sathkumara, B.L.; et al. (Ceylon College of Physicians, 2019)
Objectives: Population ageing is a world phenomenon affecting many sectors including health. High prevalence of multiple co-morbidities, increased healthcare expenditure, psychological disease and social consequences are some major health problems of ageing. Study of physiology and health status among elders is an important component in geriatric care. This is a study protocol to describe overall health status and functional capacity among the elders in residential care facilities in Colombo district. Methods: Eligible elders aged over 65 years, in all residential care facilities in Colombo district, registered under the National Secretariat for elders will be included in this cross-sectional study. Data on basic demography and medical co-morbidities will be collected. Nutritional status will be assessed by 24-hour dietary recall, mini nutritional assessment and anthropometric measurements. Five fried model indicators, Montreal cognitive assessment and geriatric depression scale will be used to assess frailty, depression and cognition respectively. Timed up and go test and five times sit to stand test will be performed to assess the risk of falls and the FRAX index for osteoporotic risk assessment. Spirometry will be used to assess respiratory function. Descriptive and correlation analysis of data will be performed. Discussion: This is a comprehensive health assessment of the elderly population living in residential care facilities for elders in Colombo. The study will contribute to establish better geriatric care in Sri Lanka and will serve as a model to design an island wide study on elderly.
Keywords: Elderly population; Elderly homes; Geriatric health